Perceived current status of government programs in enhancing business growth and developments of MSME's the case of Negosyo Center of DTI in Tacloban City - Lacambra, Lourdes Jaiza M.; Lasap, Jasmin; Mendoza, Ma. Gracia P.; Vicencio, Allen Mae T.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are widely recognized as critical drivers of economic growth and development, both globally and in the Philippines. In support of MSMEs, the Department of Trade and Industry (DTI) implemented the Negosyo Center Program under the Go Negosyo Act (R.A. 10644) to provide streamlined services and support for MSMEs, This study determined the Negosyo Center's perceived current status in enhancing MSMEs business growth and development. Using a convergent parallel mixed-method design, quantitative data were gathered through an assisted face-to-face survey with MSMEs, and qualitative data were collected through semi-structured one-on-one interviews with Negosyo Center's Project Team. Findings revealed that MSME owners generally held favorable views of the services provided and strongly agreed on the perceived contribution of assistance received, particularly in variables such as Revenue Growth, Number of Employees, Market Expansion, Product or Service Innovation, and Technology Adoption, although they perceived only a moderate overall impact on their businesses. The majority reported high satisfaction with key Negosyo Center services like Registration Facilitation, Training and Seminars, Financial Support, Product or Service Innovation Support, Machinery and Equipment, Market Access, and Consultation and Mentoring, while services such as Accessibility of Information and Networking and Collaboration were perceived to have only a moderate to little impact due to the challenges experienced. The study also uncovered several implementation challenges, and despite current best practices, the Negosyo Center's Project Team was unable to specifically make targeted interventions to address the challenges faced in the implementation of the Negosyo Center program. Thus, this study recommended courses of action to be integrated into the current best practices employed by the Negosyo Center's Project Team to directly address operational challenges, enhance MSME satisfaction with Negosyo Center services, and strengthen the program's impact on MSMEs' business growth and development.
Undergraduate thesis (Bachelor in Science in Management) -- University of the Philippines, Tacloban.
Includes bibliographical references.
Keywords: Small and medium-sized enterprises -- Tacloban City; Micro; Small; Medium enterprises (MSMEs).; Negosyo center; Business growth and development; Tacloban City; Perceived effectiveness